Total Quality Management (TQM) Practices and Operational Performance in Manufacturing Company - Mohd Zaidi, Zakiah; Ahmad, Nurazwa (Research in Management of Technology and Business, 2020)
Manufacturing industry is facing challenges to deal with poor quality products, lack of customer satisfaction and supplier issues. In an effort to improve operational performance hence dealing with the challenges in manufacturing company, one approach currently adopted in many organizations is the concept of Total Quality Management (TQM) practices. Despite the claim of substantial benefits of implementing TQM, operational performance of some companies remains unsatisfying. Therefore, this study seeks to examine the relationship between TQM practices and operational performance in manufacturing industry in Malaysia. Five dimensions of TQM practices were studied which are organizational leadership, customer satisfaction and relationships, human resources focus, strategic planning and development, and supplier quality management. This research employed a quantitative research method. Survey questionnaire were randomly distributed to 364 manufacturers in Johor. The final response rate of 13.74% was achieved. The Statistical Package Social Science (SPSS) was used to run the descriptive analysis, normality test and Spearman correlation analysis. The findings showed that the level of TQM practices and operational performance is at high level. Furthermore, the results indicated that, all five dimensions of TQM practices had a significant and positive relationships with operational performance. It is suggested that the implementation of TQM practices is important in ensuring that the operational performance increases in manufacturing companies.